The Effect of Virtual Experiment Media in Direct Learning on Students' Cognitive Learning Outcomes on GLB-GLBB Material - Hermansyah Hermansyah; Fahmi Yahya; Syahriani Yulianci; I Made Sentaya; I Gusti Made Sulindra (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2022)
The use of appropriate media to facilitate student activities in learning physics is still very minimal at this time. This has an impact on the lack of enthusiasm of students in learning physics which will indirectly affect their learning outcomes. The integration of interactive multimedia in direct learning is an alternative solution in carrying out activities in physics learning. This quasi-experimental research aims to determine the effect of using interactive multimedia in direct learning on students' cognitive learning outcomes for GLB-GLBB material. The research design used was a pretest-posttest control group design with purposive sampling as sampling technique. The respondents for this research were 45 students of Class X MIA in one of the senior high schools in Sumbawa Regency, which were divided into 2 groups, experimental and control. Data analysis used the ANOVA test to determine the significance of the difference in the mean of the two groups. The question instrument used to collect data on students' cognitive learning outcomes is in the form of descriptions with a total of 5 items. The ANOVA test results obtained a significance of 0.175, where the significance value is greater than 0.05. Based on these results, it can be concluded that the use of interactive multimedia that is integrated in direct learning does not significantly affect students' cognitive learning outcomes for GLB-GLBB material.